The gay cake controversy in the United Kingdom and Italian inertia. Issue 6 (December 2022) - Breda, Vito; Frau, Matteo
In Lee v. United Kingdom, the European Court of Human Rights left gay people partially unprotected against discrimination in commercial transactions in the United Kingdom and, by analogy, in other legal systems, such as the Italian system, where such protection is absent. In this article, it will be argued that the lack of substantive engagement by the European Court of Human Rights should be considered a missed opportunity for the development of European legal systems that do not grant full anti-discrimination protection to gay people.